2019
DOI: 10.1097/rli.0000000000000501
|View full text |Cite
|
Sign up to set email alerts
|

Interscanner and Intrascanner Comparison of Virtual Unenhanced Attenuation Values Derived From Twin Beam Dual-Energy and Dual-Source, Dual-Energy Computed Tomography

Abstract: Dual-energy techniques vary in reproducibility of VUE attenuation values. In the current study, tbDECT demonstrated higher variation in VUE HU measurements in comparison to a dsDECT. Virtual unenhanced HU measurements cannot be reliably compared on follow-up CT, if these 2 different dual-energy CT platforms are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
(55 reference statements)
4
17
0
Order By: Relevance
“…This finding adds to recent studies which elucidated that VNC provide reasonable approximations of TNC, yet might lack the accuracy needed for dedicated threshold-based lesion characterization [25]. However, the differences between VNC and VNC we found were mostly within a 10 HU margin that has previously deemed acceptable for TNC/VNC agreement [21]. Moreover, the lower TNC/VNC agreement in venous vessels was not reflected in the qualitative results.…”
Section: Discussionsupporting
confidence: 52%
“…This finding adds to recent studies which elucidated that VNC provide reasonable approximations of TNC, yet might lack the accuracy needed for dedicated threshold-based lesion characterization [25]. However, the differences between VNC and VNC we found were mostly within a 10 HU margin that has previously deemed acceptable for TNC/VNC agreement [21]. Moreover, the lower TNC/VNC agreement in venous vessels was not reflected in the qualitative results.…”
Section: Discussionsupporting
confidence: 52%
“…We might assume that results may differ at other, higher radiation dose levels. Finally, we did not assess DECT-based virtual noncontrast images, 35 which could be used to replace a separate noncontrast scan, thus further reducing the radiation dose to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…These allow for the reconstruction of images that subtract the iodine-associated attenuation resulting in so-called virtual non-contrast (VNC) images 12 20 . While several studies demonstrated the general functionality of VNC 21 26 ; studies which systematically investigating the impact of different patient-associated sizes, image acquisition and reconstruction parameters are sparse. Yet, it is essential to understand confounding factors for the evaluation of VNC performance 8 11 , 27 – 30 .…”
Section: Introductionmentioning
confidence: 99%